2010
DOI: 10.1590/s0102-09352010000300011
|View full text |Cite
|
Sign up to set email alerts
|

Uso de viscoelásticos na facoemulsificação em cães portadores de catarata: efeitos sobre a pressão intraocular, a morfologia das células endoteliais e a espessura corneana

Abstract: RESUMOAvaliaram-se as células endoteliais, a espessura corneana e a pressão intraocular (PIO) de cães portadores de catarata madura, empregando-se viscoelástico à base de hialuronato de sódio 3% e sulfato de condroitina 4% e hidroxipropilmetilcelulose 2%, utilizando-se 20 cães, distribuídos entre os dois grupos dos viscoelásticos. A técnica cirúrgica adotada foi a da facoemulsificação bimanual. As avaliações tonométricas foram efetuadas antes e após o ato cirúrgico, aos 1, 7, 14, 21, 28 e 60 dias de pós-operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…CHIURCIU et al (2010) reported an increase on endothelial cells area for up to 60 days following phacoemulsifi cation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CHIURCIU et al (2010) reported an increase on endothelial cells area for up to 60 days following phacoemulsifi cation.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, no difference on uveitis manifestation was observed when both groups were compared. CHIURCIU et al (2010) reported a signifi cant decrease on endothelial cells density following phacoemulsifi cation in dogs. The same was not observed in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…For the G2 patients (mature), the values differed at all times, with endothelial loss of 24% 60 days after phacoemulsification. The same was described by Chiurciu et al (2010) and Gwin Lerner, Warren, & Gum (1983) studying patients who underwent bimanual phacoemulsification (24.97%) and cataract surgery (22%), respectively. The corneal endothelium of dogs responds to surgical trauma similarly to that of humans, maintaining the functional monolayer with increased cell size and migration (Mencucci.…”
Section: Discussionmentioning
confidence: 67%
“…It begins immediately after trauma or exposure to allergens or toxins so was expected immediately after phacoemulsification (Munger, 2009). There were no postoperative complications identified such as fibrovascular membranes, growth of lenticular fibers, lenticular epithelial membranes, or endophthalmitis (Munger, 2009) It can be inferred that the presence of immature or mature cataracts does not influence the density values or cell area of the corneal endothelial cells, as the values obtained preoperatively did not differ between the groups and were not as described by Chiurciu et al (2010) and Pigatto et al (2006).…”
Section: Discussionmentioning
confidence: 99%